Integrating Artificial Intelligence in Emotional Intelligence, Self-Awareness and Mental Health in Educational Settings in Nigeria - Adaobi Jennifer Iloakasia; Nakhma'ussolikhah Nakhma'ussolikhah (Universitas Islam Bunga Bangsa Cirebon, 2024)
The teaching of English Language in tertiary institutions has continued to face challenges due to overdependence on traditional methods that limit students’ engagement and comprehension. Despite the global shift towards technology-driven learning, many lecturers encounter difficulties in adopting digital instructional tools, often due to inadequate facilities, poor internet access, unstable electricity supply, and limited technical skills. The study employed a descriptive survey design to examine the use, challenges, and effectiveness of digital instructional tools in English Language teaching in tertiary institutions. A sample of 160 lecturers was selected, and data were gathered using a validated self-structured questionnaire divided into demographic and research sections, with responses rated on a 4-point Likert scale. Reliability was established through Cronbach’s alpha. Descriptive statistics such as frequency, percentage, mean, and standard deviation were used to analyze research questions, with 2.50 as the decision benchmark. Hypotheses were tested using ANOVA. The findings revealed that lecturers moderately utilized digital instructional tools in English Language teaching, with high usage of projectors, multimedia, and video resources (mean = 3.36–3.46). However, integration faced challenges such as unstable electricity (mean = 3.53), inadequate technology (3.25), poor internet (3.08), high maintenance cost (3.30), and need for training (3.29). Despite these, lecturers perceived digital tools as effective in enhancing engagement (3.22), improving comprehension (3.03), saving time (3.26), extending practice beyond class (3.26), and improving outcomes (3.32). ANOVA showed no significant differences in utilization (p = .917) or challenges (p = .918), but significant differences in effectiveness perceptions (p = .022). The study concludes that digital instructional tools are indispensable in English Language teaching and recommends improved institutional support, training, and provision of modern facilities to strengthen technology integration.